Role of nuclear receptors NlHR3 and NlFTZ-F1 in regulating molting and reproduction in Nilaparvata lugens (stål) - Li, Kailong; Liu, Kanghong; Wang, Xing; Ma, Mingyong; Luo, Xiangwen; Chen, Wuying; Chen, Ang; Peng, Zhaopu; Zhang, Deyong (Frontiers in Physiology, 2023)
The nuclear receptors HR3 and FTZ-F1 are highly conserved and function to regulate molting and reproduction in both hemimetabolous and holometabolous insects. However, their roles in Nilaparvata lugens are largely unknown. In the present study, we discover that NlHR3 and NlFTZ-F1 are activated in the nymph stages by ecdysone signaling. Transcription disruption of NlHR3 and NlFTZ-F1 expression prevents nymph ecdysis and metamorphosis, which leads to abnormal appearance, malformed ovaries and lethal phenotype. In addition, we demonstrate that NlHR3 and NlFTZ-F1 regulates molting and reproduction by interacting with the intrinsic 20E and JH signaling pathway. Our works offer a deep insight into the action mechanisms of HR3 and FTZ-F1 in insects. Besides, NlHR3 and NlFTZ-F1 could be properly exploited as potential target genes for developing RNAi-based pesticides to control N. lugens.